Analisis SEMA (Surat Edaran Mahkamah Agung) Nomor 3 Tahun 2023 Angka 3 tentang Hak Waris Anak yang Terlahir dari Pernikahan Siri Berdasarkan Wasiat Wajibah Perspektif Fikih Mawaris - Nur Safrina; Endri Yenti (AHKAM, 2026)
The widespread practice of unregistered marriage (pernikahan siri) in society raises legal issues, particularly regarding the status and inheritance rights of children born from such marriages. Although an unregistered marriage is considered valid under Islamic law when it fulfills the pillars and requirements of marriage, it does not receive administrative recognition under state law because it is not officially registered, thereby creating uncertainty regarding the fulfillment of children’s inheritance rights. This study aims to analyze the status of the inheritance rights of children born from unregistered marriages according to Islamic inheritance jurisprudence (fiqh al-mawarith) and examine the application of wasiat wajibah as a positive-law solution, as stipulated in Supreme Court Circular Letter Number 3 of 2023. The study employed a normative legal method with a qualitative approach through a literature review of Islamic jurisprudential literature, scholarly opinions, the Compilation of Islamic Law, and relevant laws and regulations. The findings indicate that children born from unregistered marriages retain inheritance rights under Islamic law because their lineage is considered legitimate when their parents’ marriage has fulfilled the pillars and requirements of marriage. However, within the context of positive law, these children do not directly acquire inheritance rights; therefore, the fulfillment of their rights is pursued through wasiat wajibah. The application of wasiat wajibah is regarded as an effort to realize public benefit and social justice, although conceptually it is not entirely consistent with the principles of inheritance distribution in Islamic inheritance jurisprudence. This study concludes that Supreme Court Circular Letter Number 3 of 2023 provides an alternative form of legal protection for children born from unregistered marriages through wasiat wajibah, while also demonstrating differences in legal construction between Islamic law and positive law in determining children’s inheritance rights. These findings contribute to the development of Islamic family law studies and may serve as a conceptual foundation for formulating more equitable protection of children’s civil rights.